The existence of local products (production/processing) in special economic area of Mandalika Lombok - Masrun, Masrun; Ilhamudin, Muhamad (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
The purpose of this study is to dig deeply by doing identification of various local products; develop local product development strategies; and explain the advantages and disadvantages of local products in the Mandalika Special Economic Zone. The research was conducted qualitatively, data were obtained from: literature study; field data, through: in-depth interview (indeptinterview), observation, and documentation. The results of the study: 1) Local products in the Mandalika Special Economic Zone are identified, among others: goods/production products, namely culinary, processing products, such as shrimp paste and chips. 2) Local product development strategy in Mandalika Special Economic Zone: promoting through print and online media, developing products that have appeal, cooperation with sthakeholders, provide adequate facilities and infrastructure, local product development (goods/processing) can implement the marketing strategy. 3) Advantages: have a positive impact on the economic conditions of the community/SMEs; the price is relatively affordable for consumer; the existence of district government regulations, village regulations, local regulations (awiq-awiq). Weaknesses: visitors in the Mandalika Special Economic Zone who rame not every time/day; the raw materials are limited; poor business management; promotion/marketing of local products is still lacking; business capital is relatively small; and lack of counseling and field guidance by relevant agencies.